Development of Bunching System for High Intensity Cyclotron at CIAE. Issue 11 (2nd November 2022) - Li, Pengzhan; Zhang, Tianjue; Jia, Xianlu; Ji, Bin; Song, Guofang; Li, Ming; Wei, Junyi
ABSTRACT: A new double-gap buncher is designed for the CYCIAE-10 cyclotron in order to get the high-intensity proton beam with the order of mA. RF simulation is carefully performed to achieve a deep quantitative analysis of the equivalent capacitance and electrical field distribution. Uniform electrical field technology is verified by EM field simulation to get an electrical field uniformity of 94.67%. Type L matching circuit is used to transfer the loading reactance to 50 Ohms. Variable vacuum capacitor with 5–50 pF is selected for its small power loss and the convenience of commissioning. Dynamic calculation of the buncher and mechanical design are also presented in this paper. The open-loop bench test shows that 370 Vpeak RF voltage is established in the central electrode with power consumption of 37 W. Alternative redesign and online test are carried out, and more than 1 mA H − beams are achieved on the inner target, which verify the buncher design. Graphical Abstract: uf0001